PENGARUH MODEL PEMBELAJARAN BLENDED LEARNING DENGAN PENDEKATAN REALISTIC MATHEMATICSS EDUCATION (RME) TERHADAP PEMAHAMAN KONSEP MATEMATIKA - YETTI WIDIARTI; HANIFAH HANIFAH; SALEH HAJI (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2022)
This study aims to determine whether there is an effect of the learning model Blended Learning with the Realistic Mathematics Education (RME) approach on students' conceptual understanding. This type of research is an experimental study with a quasi-experimental design which was carried out at The Junior High School Student Number 11 Bengkulu City in the even semester of the 2020/2021 school year with the research population being all students of class VIII totaling 248 students and the research sample totaling 60 students consisting of 2 classes namely class VIII.E as the experimental class and VIII.F as the control class. Based on the Mancova analysis test, it shows that there is a significant effect of thelearning model Blended Learning with the approach Realistic Mathematics Education on understanding concepts. The understanding of students' mathematical concepts in the class taught with thelearning model Blended Learning with the approach Realistic Mathematics Education is higher than the class taught with the conventional model. The average understanding of concepts in the experimental class is 75.67 while in the control class it is 67.83. ABSTRAKPenelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh model pembelajaran Blended Learning dengan pendekatan Realistic Mathematics Education (RME) terhadap pemahaman konsep siswa. Jenis penelitian ini adalah penelitian eksperimen dengan desain quasi eksperimental yang dilaksanakan di SMPN 11 Kota Bengkulu pada semester genap tahun pelajaran 2020/2021 dengan populasi penelitian adalah seluruh siswa kelas VIII yang berjumlah 248 siswa dan sampel penelitian berjumlah 60 siswa yang terdiri dari 2 kelas yaitu kelas VIII.E sebagai kelas eksperimen dan kelas VIII.F sebagai kelas kontrol. Berdasarkan uji analisis Mancova, menunjukan bahwa terdapat pengaruh signifikan model pembelajaran Blended Learning dengan pendekatan Realistic Mathematics Education terhadap pemahaman konsep. Pemahaman konsep matemaika siswa pada kelas yang diajar dengan model pembelajaran Blended Learning dengan pendekatan Realistic Mathematics Education lebih tinggi dibandingkan kelas yang diajar dengan model konvensional. Rata – rata pemahaman konsep pada kelas eksperimen sebesar 75,67 sedangkan pada kelas kontrol sebesar 67,83.